Colistin Plus Carbapenem versus Colistin Monotherapy in the Treatment of Carbapenem-Resistant Acinetobacter baumannii Pneumonia - Shi H (Infection and Drug Resistance, 2019)
HyeJin Shi,1 Jin Seo Lee,2 So Yeon Park,2 Yousang Ko,2 Joong Sik Eom1 1Division of Infectious Diseases, Gil Medical Center, Gachon University College of Medicine, Incheon, Republic of Korea; 2Division of Infectious Diseases, Kangdong Sacred Heart Hospital, Hallym University School of Medicine, Seoul, Republic of KoreaCorrespondence: Jin Seo LeeDivision of Infectious Diseases, Kangdong Sacred Heart Hospital, Hallym University School of Medicine, 150 Sungan-Ro, Gangdong-Gu, Seoul 06351, South KoreaTel +82-2-2224-2895Fax +82-2-488-0119Email rem324@naver.comPurpose: Colistin alone may not be sufficient for treating carbapenem-resistant Acinetobacter baumannii (CRAB); thus, efforts are needed to increase treatment success rates. We compared the effects of colistin plus carbapenem therapy versus colistin monotherapy in treating pneumonia caused by CRAB and attempted to identify specific populations or factors that could benefit from combination therapy.Methods: We retrospectively collected data on cases of CRAB pneumonia. The patients were divided into colistin plus carbapenem therapy and colistin monotherapy groups. The primary outcome was 14-day mortality. The secondary outcomes were in-hospital mortality, clinical improvement at days 2 and 14, and microbiological improvement at day 14.Results: Of 160 cases meeting criteria for CRAB pneumonia, 83 (52%) and 77 (48.0%) were treated with carbapenem combination therapy or colistin monotherapy, respectively. Among these patients, 50 (63.3%) in the combination group and 27 (39.7%) in the monotherapy group had Acute Physiologic Assessment and Chronic Health Evaluation (APACHE) II scores >24 points (p=0.010). Overall, there was no significant difference in 14-day mortality between the combination and monotherapy groups (24.1% vs 20.8%, p=0.616). Clinical improvement and sputum-negative conversion also showed no significant difference. After adjusting for disease severity according to APACHE II score, the 14-day mortality was significantly lower in the combination group than in the monotherapy group among patients with APACHE II scores of 25–29 points (9.1% vs 53.8%, P=0.020).Conclusion: Despite more severe conditions, compared with colistin monotherapy, colistin plus carbapenem combination therapy showed equivalent primary mortality outcome in treating CRAB pneumonia. Combination therapy was more effective in patients with APACHE II score ranging from 25 to 29 points.Keywords: carbapenem-resistant Acinetobacter baumannii, CRAB, pneumonia, colistin, combination therapy, risk factor